2012
DOI: 10.1258/ar.2012.120049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Contrast-Enhanced Intraoperative Ultrasound on Operation Strategy in Case of Colorectal Liver Metastasis

Abstract: Background Surgical treatment is the only option for long-term survival in patients with colorectal liver metastasis (CRLM). Contrast-enhanced CT and MRI are usually used for preoperative liver imaging. The initial surgical strategy for liver resection is based upon these findings. Further optimization of the surgical strategy by contrast-enhanced intraoperative ultrasound (CE-IOUS) might further improve the surgical outcome. Purpose To evaluate the current impact of CE-IOUS with SonoVue® on the initial surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 108 publications
(163 reference statements)
1
33
0
1
Order By: Relevance
“…The results of intraoperative contrast-enhanced US (CE-IOUS) are controversial. 25 Schulz et al 26 found 31 additional metastases over 369 tumors (8%) by using intraoperative CE-IOUS. These findings were not confirmed by Ferrero et al 10 or Torzilli.…”
Section: Discussionmentioning
confidence: 99%
“…The results of intraoperative contrast-enhanced US (CE-IOUS) are controversial. 25 Schulz et al 26 found 31 additional metastases over 369 tumors (8%) by using intraoperative CE-IOUS. These findings were not confirmed by Ferrero et al 10 or Torzilli.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment included computed tomography (CT) of the abdomen and chest with the addition of magnetic resonance (MR) or ultrasonography with contrast when resectability could not be determined after CT. Positron emission tomography (PET) became available in 2009 and was used to assess extrahepatic disease in selected cases. Intraoperative contrast-enhanced ultrasonography (CEU) was used in every procedure after 2007 to assess resectability and tumor expansion as previously described [10]. Preoperative carcinoembryonic antigen (CEA) levels were determined in all patients in the most recent 5-year period.…”
Section: Methodsmentioning
confidence: 99%
“…Planning for the optimal treatment approach for CRLM, both operative and non‐operative, requires accurate assessment of liver lesions and liver parenchyma . The ability of a surgeon to assess whether lesions are resectable impacts on patient prognosis, as surgical resection is the main determinant of long‐term outcome in this setting .…”
Section: Non‐enhanced and Ce‐ious Techniquesmentioning
confidence: 99%